A study on agricultural engineering equipment in South Tamilnadu using linear regression - Chandrakumar Thangavel; Ramya Thangavel; Karthik Chandran; Gunnam Suryanarayana; Subrata Chowdhury; Nguyen Duc Uyen; Thi-Thu Nguyen; Duc-Tan Tran (Institute of Advanced Engineering and Science, 2022)
Economic growth in India purely depends on the Indian agricultural sector. In developing countries, the mechanization of agriculture plays a vital role in productivity. The research focuses on identifying which farmers in South Tamilnadu mostly use agricultural machinery. In this paper, we have taken farmer names and mobile numbers, choice of implement requirement into consideration by collecting the real data through DBT portal (https://agrimachinery.nic.in). This research work deals with five southern districts in Tamilnadu, namely Dindigul, Madurai, Theni, Ramnad, and Virudhunagar, in which we have predicted which machinery is suitable for that area. The linear regression model was used in this research by testing and training the dataset in all five data frames to get efficient results. Prediction of each data frame reveals the efficient working of the particular machinery for that specific area due to the different geographical features.